Thrice-born Dionysos: an analysis of the birth narrative of Dionysos in Nonnos of Panopolis' Dionysiaca - Mackay, Danielle Louize (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
The following paper aims to analyse lines 660 "“ 774 of Euripides' Bacchae paying close attention to the representation of the bacchants in the account given to Pentheus by the herdsman.1 Accompanying the translation is a brief commentary further elaborated and discussed in the paper below. The purpose of this paper is to investigate how the Theban women are portrayed in the hills outside of Thebes and the implications this might for the inherent conception of the supposed structure of the polis and the oikos. Dionysos' arrival in Thebes hails a systematic disruption of the social order of the Theban polis. His presence causes an inverting of all that is familiar to the Thebans, the unknown becomes known and the known reveals itself as unknown. Euripides' Bacchae was first performed at the City Dionysia in 405 BCE, in the year after the tragedian's death. The play dramatises the arrival of the god Dionysos to Thebes to exact vengeance on those responsible for his mother's death and to establish his mysteries there (line 24f & 47f). Before one can begin any analysis of the text, it is important to establish the context established by the play, as this context is important to a fuller understanding of the text.
Keywords: Dionysus (Greek deity); Zeus (Greek deity); Nonnus, of Panopolis; Mythology, Greek; Epic poetry; Birth (Philosophy) in literature; Late antiquity; Bacchus